Significant influence of the design of the rowing ergometer on elite athlete kinematics - Hislop, S.; Cummins, K.; Bull, A. M. J.; McGregor, A. H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
Rowing injuries and performance have been attributed to the kinematics and kinetics of ergometer rowing. The aim of this study was to investigate these parameters on two commonly used rowing ergometers: one with a fixed-head design and one with a floating-head design. Using electromagnetic motion sensors and load cells, the kinematics and kinetics of ten elite male athletes (mean age, 22.8 ± 3.5 years) rowing on the two different ergometers were assessed. This revealed that the floating-head design produced a greater stroke length (p < 0.05) but higher stroke rate (p < 0.01) for the same rowing intensity. This was combined with significantly different rowing kinematics in which the fixed head had greater anterior pelvic rotation (p < 0.05) and greater femoral flexion (p < 0.05). The implications of these changes with respect to injury require further interpretation through a mathematical model. Since a full analysis comparing rowing kinematics on water with rowing ergometers has not been made here, no conclusions regarding which ergometer simulates rowing on water can be made.